Structure behavior of reinforced concrete beam-slab assemblies subjected to perimeter middle column removal scenario. (1st April 2020) - Yu, Jun; Luo, Li-zhong; Fang, Qin
Highlights: Collapse behavior of RC beam-slab assemblies studied with static-determinate set-up. Load transfer mechanisms against collapse illustrated at different deformation stages. Catenary action of perimeter beams not dominated by pure axial tension. Seismic design and rebar types affecting progressive collapse behavior of assemblies. Progressive collapse resistance of assemblies affected by loading positions in testing. Abstract: The perimeter columns of framed structures are more vulnerable to terrorist attacks due to accessibility. The beams and slabs above the damaged columns are the primary structural members to redistribute gravity load to avoid progressive collapse. Therefore, to investigate the structural behavior of reinforced concrete (RC) beam-slab assemblies against progressive collapse introduced by a perimeter middle column removal scenario, an experimental program and numerical analyses were carried out in this paper. Three 3/10 scaled specimens, each of which consisted of two square slab panels and seven beams, were tested with equivalent uniformly distributed loading (UDL) achieved by a 12-loading apparatus. High-fidelity finite element models were used to conduct parametric studies after the validation, recheck the validity of the loading apparatus and highlight the effect of loading positions. The concerned parameters include the geometric parameters of beams caused by different seismic design intensity, the slab thickness and reinforcement ratio, and the type of reinforcing bars (i.e. deformed and plain). The results indicate that progressive collapse is resisted by compressive arch action and flexural action of the beams and slabs connecting the stub above the removed column at small deformation stage, whereas catenary action of longitudinal beams and tensile membrane action of slabs are more prevailing at large deformation stage. Moreover, higher seismic design intensity results in a larger resistance at small deformation stage, and plain bars cause larger deformation capacity. Finally, loading positions approaching the stub above the removed column tends to show smaller structural resistance.